Demam Tifoid pada Seorang Pasien Usia 21 Tahun: Laporan Kasus - Abrila Tamara Putri; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2026)
Typhoid fever is an endemic infectious disease in Indonesia caused by systemic infection with Salmonella typhi and transmitted through the fecal–oral route. This disease has become a significant contributor to morbidity and mortality. Clinical manifestations, diagnostic approaches, comprehensive management, and preventive education are discussed in this case report. A 21-year-old female patient presented to a primary healthcare center with complaints of a step-ladder pattern fever for seven days, accompanied by nausea and vomiting, dry cough, and joint pain. A history of irregular dietary habits and poor hygiene practices, including frequent consumption of street food and inadequate hand hygiene before meals, were identified as major risk factors for fecal–oral transmission. Physical examination revealed a moderately ill general condition, coated tongue, and tenderness in the epigastric region. The diagnosis of acute typhoid fever was established based on serological examination using the Widal test, which demonstrated an elevated Salmonella Typhi O antibody titer of 1:320. Empirical pharmacological management included first-line antibiotic therapy with cefixime for intracellular bacterial eradication, antipyretic treatment with paracetamol, and antiemetic therapy. Non-pharmacological management consisted of strict bed rest to reduce metabolic demands, oral rehydration therapy, and dietary modification with a soft, low-fiber diet. Preventive education focused on modifying environmental and personal risk factors, including proper handwashing with soap, maintaining food sanitation to prevent contamination by fly vectors, and boiling drinking water thoroughly to reduce the risk of recurrent infection and interrupt disease transmission within the community. Early diagnosis and appropriate management are essential to prevent potentially life-threatening complications.